ChemInform Abstract: Catalytic Transformation of Bio‐Derived Furans to Valuable Ketoacids and Diketones by Water‐Soluble Ruthenium Catalysts. Issue 6 (21st January 2016) - Gupta, Kavita; Tyagi, Deepika; Dwivedi, Ambikesh D.; Mobin, Shaikh M.; Singh, Sanjay K.
Abstract: Bio‐derived furans are efficiently and under moderate reaction conditions transformed into levulinic acid (III) and diketones [(II) and (IV)], resp., using recyclable and water‐soluble ruthenium(II) complexes as catalysts.